Hydration in older adults: The contribution of bioelectrical impedance analysis. (June 2014) - Goldberg, Lynette R.; Heiss, Cynthia J.; Parsons, Susan D.; Foley, Amanda S.; Mefferd, Antje S.; Hollinger, Deborah; Parham, Douglas F.; Patterson, Jeremy
Abstract The sensory and gastrointestinal changes that occur with ageing affect older adults' food and liquid intake. Any decreased liquid intake increases the risk for dehydration. This increased dehydration risk is compounded in older adults with dysphagia. The availability of a non-invasive and easily administered way to document hydration levels in older adults is critical, particularly for adults in residential care. This pilot study investigated the contribution of bioelectrical impedance analysis to measure hydration in 19 older women in residential care: 13 who viewed themselves as healthy and six with dysphagia. Mann-Whitney U analyses documented no significant between-group differences for Total Body Water (TBW), Fat Free Mass (FFM), Fat Mass (FM), and percentage Body Fat (%BF). However, when compared to previously published data for age-matched women, the TBW and FFM values of the two participant groups were notably less, and FM and %BF values were notably greater than expected. If results are confirmed through continued investigation, such findings may suggest that long-term care facilities are unique environments in which all older residents can be considered at-risk for dehydration and support the use of BIA as a non-invasive tool to assess and monitor their hydration status.